PENGARUH KONSENTRASI BIOURINE SAPI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI (Brassica juncea L.) - Abdul Haris; Saida Saida; Abdullah Abdullah; Tasrif Tabrani (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2023)
This study aims to determine the effect of giving various concentrations of cow bio urines on the growth and yield of mustard plants grown on bed media. This research was conducted in Samaulue Village, Lanrisang District, Pinrang Regency, South Sulawesi Province. This study took place from December 2021 to February 2022. The study used a randomized block design consisting of 3 levels of treatment, namely 150 ml/liter, 250 ml/liter, and 300 ml/liter, and treatment without urine. Each treatment was repeated three times to get 12 experimental units. The results showed that using a concentration of 250 ml/liter cow urine fertilizer could increase the growth and yield of mustard plants. The average plant height was 38.98 cm, the wet weight of the plant was 235.67 g, the dry weight of the plant was 23.67 g and the consumption weight was 234.33 g.